Decompressive Craniectomy for Intracranial Pathologies in the Intensive Care Unit : Effects on Mortality and Clinical Course - Ahmet Sari; Osman Ekinci; Selen Bozdemir; Recep Balık; Ahmet Sait Bulut; Süheyla Abitağaoğlu; Fatih Kılıç; Saliha Erkan; Fethi Gül; Burçin Doruk Oktay; Yelda Balık; Feyza Kargın; et al. (Journal of Korean Neurosurgical Society, 2026)
Objective : Decompressive craniectomy (DC) is a surgical procedure in which a portion of the skull overlying edematous and vulnerable brain tissue is removed to reduce intracranial pressure. In cases where all other treatment modalities fail, DC can be life-saving. However, this procedure is not a “panacea;” it can prolong the death process and condemn the patient to a life in need of care, with severe neurological sequelae.Methods : This multicenter, retrospective study recorded patients’ comorbidities, Glasgow coma scale (GCS), Acute physiology and chronic health evaluation II (APACHE II) and Sequential organ failure assessment (SOFA) scores, as well as relevant laboratory parameters. Patients were categorized into three groups according to the Glasgow outcome scale.Results : Among 201 patients, 41.3% expired, 33.8% survived with severe vegetative sequelae, and 24.9% had mild to moderate sequelae. Non-survivors had significantly lower preoperative and postoperative GCS scores (median 7 vs. 9, p=0.010; 3 vs. 10, p